Catalytic Hydrogenation of Levulinic Acid Using Ruthenium Dioxide Supported on Zeolites - Dialia A. Abusuek (AIDIC Servizi S.r.l., 2021)
Levulinic acid (LA) is a substance, which can be obtained from cellulosic biomass via acid hydrolysis. Hydrogenation of LA to gamma-valerolactone (GVL) is one of the most promising reactions in the field of biomass valorization to fine chemicals and liquid transportation fuels. In this work, the reaction of LA hydrogenation to GVL was carried out using series of Ru-containing catalytic systems based on zeolites (HZSM-5, HBeta, HY, HMordenite). It was shown that synthesized catalyst based on zeolite HZSM-5, containing RuO2 as an active phase, can provide high yields of GVL (up to 98 %) for less than 1 h upon relatively mild reaction conditions (100 °C, 1 MPa). Moreover, it was shown that the observed catalytic activity and stability depends on the concentration of RuO2 on the catalyst surface as well as on distribution of catalytically active phase.